The Last Year Before Graft Failure Negatively Impacts Economic Outcomes and is Associated With Greater Healthcare Resource Utilization Compared With Previous Years in the United Kingdom: Results of a Retrospective Observational Study. Issue 5 (May 2019) - Muduma, Gorden; Aluvihare, Varuna; Clancy, Marc; de Nigris, Enrico; Whitlock, Carolyn; Landeira, Margarita; Nazir, Jameel
Abstract : Background: Kidney and liver transplantation is the standard of care for end-stage renal or liver disease. However, long-term survival of kidney and liver grafts remain suboptimal. Our study aimed to understand the healthcare resources utilized and their associated costs in the years before graft failure. Methods: Two noninterventional, retrospective, observational studies were conducted in cohorts of kidney or liver transplant patients. Once identified, patients were followed using the UK Clinical Practice Research Datalink linked to the Hospital Episode Statistics databases from the date of transplantation to the date of the first graft failure. Total healthcare costs in the year before graft failure (primary endpoint) and during years 2–5 before graft failure (secondary endpoint) were collected. Results: A total of 269 kidney and 81 liver transplant patients were analyzed. The mean total costs were highest for all resource components in the last year before graft failure, except for mean costs of immunosuppressive therapy per patient, which decreased slightly by index date (ie, graft failure). The mean total healthcare costs in the last year before graft failure were £8115 for kidney and £9988 for liver transplant patients and were significantly ( P < 0.05) higher than years 2–5 before graft failure. Mean healthcare costs for years 2, 3, 4, and 5 before graft failure were £5925, £5575, £5469, and £5468, respectively, for kidney, and £6763, £7042, £6020, and £5651, respectively, for liver transplant patients. Conclusions: Total healthcare costs in the last year before graft failure are substantial and statistically significantly higher than years 2–5 before graft failure, in both kidney and liver transplant patients. Our findings show the economic burden placed on healthcare services in the years before graft failure. Abstract : Supplemental Digital Content is available in the text.